The flexible job-shop scheduling problem considering deterioration effect and energy consumption simultaneously. (September 2019) - Wu, Xiuli; Shen, Xianli; Li, Congbo
Highlights: A multi-objective optimization model for the proposed problem is established. The actual processing time is determined by a step-deterioration effect model. A scheduling heuristic for saving energy without delaying makespan is designed. Hybrid pigeon-inspired optimization and simulated annealing algorithm is developed. Abstract: In the practical production, the processing time of jobs is not deterministic whereas grow due to deterioration effect. Besides, with the increasing environmental pollution problems, manufacturing companies cannot only focus on economic indicators, hence research on green manufacturing has received much attention. Hence, we study the flexible job-shop scheduling problem considering deterioration effect and energy consumption simultaneously. To begin with, the step-deterioration effect model is formulated to determine the actual processing time. An energy consumption model is employed to compute the machine's energy consumption which in different states. A multi-objective optimization model is formulated for the flexible job-shop scheduling problem considering deterioration effect and energy consumption simultaneously. Then, a multi-objective hybrid pigeon-inspired optimization and simulated annealing algorithm is developed to solve the problem. In the developed algorithm, an energy-saving scheduling heuristic for saving energy without delaying the makespan is proposed. Finally, the experiment results show that the proposed model and the developed algorithm can solve the proposed problem effectively and efficiently.